Comparison of Outcomes and Factors Responsible for the Difference in Outcomes of Patients With Ischemic Versus Hemorrhagic Stroke - Bibi, Raheela; Ali, Syed Ahsan (Biological and Clinical Sciences Research Journal, 2025)
Stroke remains a leading cause of morbidity and mortality worldwide. Understanding stroke types' distribution and associated risk factors is essential to improve prevention and treatment strategies. Objective: To assess the frequency of different types of stroke, identify the factors contributing to stroke, evaluate their outcomes, and compare the prevalence of these factors across various stroke types. Methods: The study, conducted at The Aga Khan University Hospital from 1st July to 31st December 2023; included male and female patients aged 30 to 85 years admitted with a first ischemic or hemorrhagic stroke. Exclusion criteria were previous stroke, transient ischemic attacks, normal radiology, or intracranial hemorrhage due to brain tumor, trauma or post-surgery. Data was collected via a proforma with patient details, stroke confirmation, and risk factors (diabetes, hypertension, ischemic heart disease, dyslipidemia, and atrial fibrillation). Outcomes were assessed using the Modified Rankin Scale (mRS). Data analysis was performed using SPSS, comparing ischemic and hemorrhagic stroke subgroups using the t-test and post-stratification analysis via the chi-squared test, with significance set at p ≤ 0.05. Results: A total of 140 patients with a first episode of stroke (ischemic or hemorrhagic) were enrolled, with 89 males and 51 females. The mean age was 60 ± 14.03 years, and the stroke types were evenly split: 50% ischemic (70 cases) and 50% hemorrhagic (70 cases). Diabetes was present in 56% of participants, and hypertension in 82%. Ischemic heart disease affected 35%, atrial fibrillation 17%, and dyslipidemia 42%. Diabetes was significantly associated with ischemic stroke (p = 0.041), while hypertension (p = 0.825), ischemic heart disease (p = 0.595), and atrial fibrillation (p = 0.178) showed no significant association. Dyslipidemia had a highly significant association with ischemic stroke (p = 0.000). The mean Modified Rankin Scale (mRS) score for ischemic stroke patients was 2.16 ± 1.519, indicating slight to moderate disability, while hemorrhagic stroke patients had a higher mean score of 4.50 ± 1.164, reflecting more severe disability (p = 0.000). Ischemic stroke patients had a shorter mean hospital stay (3.04 ± 1.324 days) compared to hemorrhagic stroke patients (6.73 ± 4.603 days), with this difference being statistically significant (p = 0.000). Of the 140 patients, 14 died, with cardiopulmonary arrest being the leading cause of death (12 cases), followed by hypoxic respiratory failure/aspiration pneumonia and respiratory failure (1 case each). Conclusion: The study highlights the need for further investigation into hypertension and ischemic heart disease while reinforcing that hemorrhagic strokes cause more severe disability and prolonged recovery times.